2012
DOI: 10.1017/s1368980012003060
|View full text |Cite
|
Sign up to set email alerts
|

Does tracking of dietary behaviours differ by parental education in children during the transition into adolescence?

Abstract: Objective: The present study investigates the changes and tracking of dietary behaviours in Norwegian 11-year-olds and examines the association between parental education and dietary tracking over a time period of 20 months. Design: Longitudinal data from the Norwegian HEalth In Adolescents (HEIA) cohort study followed up at three time points (2007)(2008)(2009). Setting: Intakes of fruits, vegetables and snacks were assessed by frequency and intakes of sugar-sweetened soft drinks and squash were assessed by fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
3
26
1
1
Order By: Relevance
“…Previous studies showed the association between parental educational levels with adolescents' diet quality, healthy eating and drinking [42,43], meaning that adolescents with higher consumption of sweetened beverages and unhealthy diet had parents with lower educational level [42]. In addition, adolescents with higher parental educational level consumed fruits and vegetables more often than adolescents of parents with lower educational levels [43].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed the association between parental educational levels with adolescents' diet quality, healthy eating and drinking [42,43], meaning that adolescents with higher consumption of sweetened beverages and unhealthy diet had parents with lower educational level [42]. In addition, adolescents with higher parental educational level consumed fruits and vegetables more often than adolescents of parents with lower educational levels [43].…”
Section: Discussionmentioning
confidence: 96%
“…We observed the association of baseline ARA with BP after 6 years of follow up. This may indicate that the adverse effects of the dietary pattern may become stronger with increasing age as dietary patterns have been shown to track from childhood to adolescence [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Adequate test-retest reliability for all the measures of dietary behavior has also previously been documented [29]. …”
Section: Methodsmentioning
confidence: 99%